Психологічні детермінанти професійного розвитку та успіху спеціаліста в умовах сучасних викликів. - Собкова, Світлана; Томюк, Мирослав (Центр професійного розвитку PsyUpgrade, 2026)
The article highlights the complex and multifaceted problem of professional personality development, as well as the issue of ensuring the subjective success of a modern specialist as one of the key strategic tasks in the context of dynamic changes in the global labor market and social instability. The purpose of the study is a thorough theoretical justification and systematic analysis of psychological determinants that directly influence the vector and effectiveness of professional development. A substantive analysis of the leading scientific approaches to the definition of the concepts of "career adaptability", "professional identity" and "success" was carried out, their interdependence and the hierarchical structure of value orientations were revealed. The basic resources of adaptability are identified and described in detail: concern as a future orientation, control as a manifestation of agency, curiosity about new opportunities, and confidence in one's own self-efficacy. Particular attention is paid to substantiating the role of digital readiness and the concept of lifelong learning as fundamental factors determining the level of competitiveness and psychological resilience of a specialist. The results of the analysis of modern empirical studies are presented, which convincingly confirm the existence of a statistically significant relationship between the types of intrinsic motivation, the degree of self-regulation development, and the ability of an individual to constructively adapt in conditions of social uncertainty and military challenges. It is proved that the subjective perception of one's own success acts as a powerful internal psychological tool that ensures the stability of professional self-consciousness, activates adaptive strategies for overcoming difficulties, and effectively prevents the emergence of professional burnout symptoms and deformations.
Keywords: професійне становлення, успішність, кар’єрна адаптивність, цифрова готовність, професійна ідентичність, саморегуляція, психологічний капітал.